QUALITY AS A STRATEGIC ADVANTAGE IN THE HOTEL AND RESTAURANT BUSINESS - Mendela, I.Ya; Mendela , Ye.М. (The actual problems of regional economy development, 2025)
The article explores quality as a strategic advantage in the hotel and restaurant business amid growing competition and the rapid, dynamic development of the hospitality industry. This topic has gained particular relevance due to ongoing transformative processes in the modern business environment, as well as the evolving and increasingly sophisticated demands and expectations of consumers. It is established that quality in today’s context acquires a comprehensive and multifaceted meaning, encompassing not only strict compliance with established service standards but also the emotional and experiential components of customer satisfaction, organizational resilience to change, and the ability to continuously adapt to innovations and emerging technologies. The purpose of this study is to determine the crucial role of quality in shaping and enhancing the competitiveness of hospitality enterprises, while also developing practical recommendations for effectively implementing strategic quality management within their daily operations. To achieve this goal, the research employs a systematic and interdisciplinary approach, thorough analysis of scientific literature, generalization of best practices from leading industry companies, and the application of comparative, structural-logical, and situational analysis methods. The results of the study confirm that high service quality is a key factor in securing long-term business success, maintaining customer loyalty, and strengthening brand reputation. Key findings include the identification of priority areas for improving quality in the hotel and restaurant sector, such as the implementation of advanced digital tools for quality monitoring and control, fostering a customer-oriented corporate culture, comprehensive staff training programs, adaptation and integration of global service standards, and the adoption of environmentally responsible and sustainable business practices. The scientific novelty of this research lies in the holistic interpretation of quality as a strategic resource capable of providing companies with a sustainable competitive advantage in today’s turbulent and rapidly changing market environment. The practical significance is reflected in the potential application of the proposed recommendations by hotel and restaurant managers to improve strategic planning, optimize service delivery, and increase overall customer satisfaction, which in turn positively influences financial performance and enhances the company’s public image and market position.